Root Induction Influenced by Strength of Tissue and Propagation Conditions in Acid Lime cv. Kagzi Lime - Prakasha, D. P.; Malkar, A.; Kulapati, H.; Shivayogi, R.; Surwenshi, Ashok; Gollagi, S. G. (International Journal of Bio-resource and Stress Management, 2025)
The investigation was conducted during the year 2019–2021 at College of Horticulture, UHS, Bagalkot in acid lime [Citrus aurantifolia (Christm.) Swingle] cv. Kagzi lime to ascertain influence of strength of tissue and propagation conditions on ability of rooting. The treatments included three types of cuttings (shoot tip, semi-hardwood and hardwood cuttings) and three propagation conditions (shade net, poly house and mist house). Coco peat filled portrays was used as the standard rooting media and container. The experiment was laid out in two factorial completely randomised design (FCRD) with three replications. There was significant influence of both strength of tissue and propagation conditions on shoot and root parameters. Combination of these two factors too had significant influence. Further, among the interactions, hardwood cutting+shade net had given maximum sprouting percentage (66.66%), number of sprouts at 30 DAP (3.67), length of shoots at 30 DAP (3.42 cm), fresh weight and dry weight (7.40 and 4.52 g), length of longest root (11.38 cm) and rooting percentage (64.81%). The interaction of hardwood cutting+mist house had produced maximum length of shoot at 60 and 90 DAP (5.46 and 9.15 cm), whereas, the minimum number of days taken for sprouting was recorded in the interaction of shoot-tip cuttings+shade net with 22.95 days. It also implied that the hardwood cuttings in combination with shade net were better to induce more shooting and rooting parameters under hot and dry weather conditions.